Avaliação da compactação do solo em sistema de cultivo lavoura-pecuária com a cultura do milho - Lima, Rubem Smith Almeida (Universidade Federal Rural do Semi-Árido, 2018)
The intensification use of the soil in agricultural areas has become a worrying factor, where the presence of animals and machines in an intense form has caused the increase in the soil density. The crop-livestock integration (ILP) is a system that use of these agricultural areas with the aim of alternating crops and animals in the same area, increasing the sustainability of production systems and improving profitability through the introduction of annual pasture cultivation. Therefore, the objective of this research was to evaluate the soil compaction effect, as a function of the physical-mechanical characteristics in areas cultivated with corn submitted to (ILP). The experiment was established in the city of Riacho dos Cavalos - PB. The area of one hectare, used for pasture during ten years in a row and currently cultivated with corn, was collected from the layers of 0 to 5, 5 to 10 and 10 to 20 cm of depth, having as parameters: water content, soil density and soil aggregate density. In general, for the studied soil, the pre-compaction of the soil increases with the reduction of the water content and, in addition, the increase of the soil density that the compression index increases with the increase of the water content and with the reduction of the soil density.
Monografia
Keywords: Pré-compressão do solo; Densidade do solo; Manejo de solo; Soil precompression; Soil density; Soil management; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA